A revision and key for the tribe Diaphorolepidini (Serpentes: Dipsadidae) and checklist for the genus Synophis - Pyron, R. Alexander; Arteaga, Alejandro; Echevarría, Lourdes Y.; Torres-Carvajal, Omar (Zootaxa, 2016)
The genus Synophis contains a number of enigmatic species, distributed primarily in the Andean highlands of northern South America. Their extreme crypsis and rarity has precluded detailed study of most species. A recent flurry of collection activity resulted in the accession of many new specimens, and the description of 4 new species in 2015, doubling the number of described taxa. However, lingering questions remain regarding the assignment of many new and historical specimens, the morphological limits and geographical ranges of the species, and their phylogenetic relationships. We analyze new and existing morphological and molecular data to produce a new molecular phylogeny and revised morphological descriptions. We validate the previously unavailable tribe name Diaphorolepidini Jenner, Pyron, Arteaga, Echevarría, & Torres-Carvajal tribe nov., describe a 9th species Synophis niceforomariae Pyron, Arteaga, Echevarría, & Torres-Carvajal sp. nov., and offer new Standard Names in English and Spanish for the group: Andean Shadow Snakes and Culebras Andinas de la Sombra, respectively. A variety of features such as vertebrae and hemipenes show an interesting range of variation in the group, which should be evaluated in future studies, to refine species limits and diagnoses further. Cryptic and undiscovered diversity undoubtedly remains, and we hope this summary provides a robust basis for future work.